MEMAHAMI FIQH SOSIAL KH. MA SAHAL MAHFUDH â€œFIQH SEBAGAI ETIKA DAN GERAKAN SOSIALâ€ - Rohmah, Nurur (JURNAL ISLAM NUSANTARA, 2017)
Understanding of fiqh (Islamic law) - by linking it to the socio-cultural conditions of Indonesian society and the spirit to restore its function as a 'guide' - continues to be made by Muslim scholars and intellectuals in the country. Throughout the years 1970 to 2000, appeared figures whose ideas and ideas surfaced. Their thinking becomes a topic in various discussion forums of Islamic law, both in the environment of pesantren, civitas academika, and in social institutions. One of these figures is KH. M.A. Sahal Mahfudh who not only carry the discourse with his book 'Nuansa Fiqh Sosial', but also has done a lot of social movements in the framework of implementation of his thinking. Fiqh as a practical derivation of the teachings of the Qur'an and Hadist actually has a position that distinguishes it apart from other scientific disciplines. Fiqh also serves as a normative foundation for behaving Muslims, either individually or collectively. However, the formalistic fiqh character is not infrequently invite a contradiction with the theological life of the human life. Therefore, KH. MA Sahal Mahfudh carries the Social Fiqh which he calls 'the development effort of madhhab qouli and manhaji in the framework of fiqh is no longer as a rigid positive law, but denotes it as social ethics and the foundation for social movements in realizing the ideals of human life , sa'adatuddaraini (happiness in the world and the hereafter).